N-Acylhydrazone Pharmacophore's Analgesic and Anti-inflammatory Profile: Recent Advancements during the Past Ten Years - Kassab, Asmaa E. (Current Pharmaceutical Design, 2024)
Due to its important biological and pharmacological properties, in the field of medicinal chemistry and drug discovery, the N-acylhydrazone motif has shown to be extremely adaptable and promising. This scaffold has become a crucial component in the synthesis of numerous bioactive agents. N-Acylhydrazones are also interesting biological and synthetic tools due to their easy and straightforward synthesis. The current review provides a summary of the analgesic and anti-inflammatory activities of N-acylhydrazone derivatives over the past ten years. A brief discussion of structure-activity relationships is also provided which may guide researchers in medicinal chemistry to develop derivatives based on N-acylhydrazone scaffold as potent anti-inflammatory candidates.
Keywords: COX-2